2011
DOI: 10.4314/sajas.v40i4.65241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extruded cotton and canola seed on unsaturated fatty acid composition in the plasma, erythrocytes and livers of lambs

Abstract: An experiment was conducted to study the effects of extruded cotton seed (ECOS) and canola seed (ECAS) in the diet of male Mehraban lambs on the concentration of unsaturated fatty acids in their plasma, erythrocytes and livers. The treatments were: (1) control (C); (2) diet C+6% ECAS, (3) diet C+6% ECOS, (4) diet C+12% ECAS, (5) diet C+12% ECOS, (6) diet C+6% ECAS+6% ECOS, (7) diet C+12% ECAS +6% ECOS, (8) diet C+6% ECAS +12% ECOS, (9) diet C+12% ECAS+12% ECOS, (10) diet C+18% ECAS+18% ECOS. A complete randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…By contrast, the bulk of the SBM oil was made up of 457.5 g kg –1 PUFAs and almost equal proportions of the TSFAs (256.0 g kg –1 ) and MUFAs: 279.0 g kg –1 . Despite the high concentration of OA in Marula nut meals and its beneficial effects in animal health and meat quality, a large amount of residual oil in the Marula meals could result in the shortening of the shelf life of feeds as a result of the rancidity that develops from lipid peroxidation. Thus, it would be ideal either to incorporate antioxidants into the feeds or to substantially reduce the residual oil content of the Marula nut meals prior to their use as feed ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the bulk of the SBM oil was made up of 457.5 g kg –1 PUFAs and almost equal proportions of the TSFAs (256.0 g kg –1 ) and MUFAs: 279.0 g kg –1 . Despite the high concentration of OA in Marula nut meals and its beneficial effects in animal health and meat quality, a large amount of residual oil in the Marula meals could result in the shortening of the shelf life of feeds as a result of the rancidity that develops from lipid peroxidation. Thus, it would be ideal either to incorporate antioxidants into the feeds or to substantially reduce the residual oil content of the Marula nut meals prior to their use as feed ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding concurs with those of Loor et al [ 31 ] who observed that dairy cattle fed 3.3 % canola oil, canolamide or blend of canola oil and canolamide had higher serum C18:1n-9 compared with those fed control diet. In addition, Ahmadi sheik et al [ 33 ] observed that lambs fed extruded canola and cotton seeds had higher plasma C18:1n-9 compared to those fed control diets.…”
Section: Discussionmentioning
confidence: 99%